Rancangan Sistem Monitoring Indicator LED Transmitter ILS di Bandar Udara Tjilik Riwut Palangkaraya - Rahim, Jamaluddin; Junaedi, Seacher (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
Monitoring indicator led equipment Instrument Landing System (ILS) plays an important role in information services for aviation safety, the situation should always be monitored to anticipate the error on . The purpose of planning to design applications based on visual basic 6.0, to monitor the change of main Tx to Tx standby Instrument Landing System (ILS \) at the airport Tjilik Riiwut Palangkaraya. Design using Microsoft Visual Basic 6.0 and connect using Wi-Fi networks. The results of this planning monitoring progress towards the turn of the main Tx to Tx stand by to be able to overcome the instability of security. Therefore, it is advisable to arrange a more sophisticated monitoring system for equipment ILS (Instrument Landing System).